HEADING TIME OF SUBSTITUTION AND NEAR-ISOGENIC LINES OF COMMON WHEAT WITH DOMINANT ALLELES Vrn-B1a AND Vrn-B1c - M. V. Emtseva; T. T. Efremova; V. S. Arbuzova (Вавиловский журнал генетики и селекции)
Heading time of substitution and near-isogenic lines (NILs) with Vrn-B1a and Vrn-B1c alleles was studied without vernalization and after 30-day vernalization in a greenhouse and in the field. Without vernalization, both in a greenhouse and in the field, plants with the Vrn-B1c allele headed several days earlier than plants with Vrn-B1a. However, plants with Vrn-B1a responded to vernalization by more pronounced heading acceleration than Vrn-B1c plants. The weak Vrn-B1a allele dominated in F1 hybrids from the cross between two NILs with the Vrn-B1c and Vrn-B1a alleles. These observations confirm the multiple allelism of the Vrn-B1 gene, responsible for the spring growth habit in wheat.